Caffeine induces a second wave of apoptosis after low dose-rate gamma radiation of HL-60 cells - Vávrová, Jirina; Mareková-Rezácová, Martina; Vokurková, Doris; Szkanderová, Sylva; Psutka, Jan (Radiation and environmental biophysics, 2003)
Most cell lines that lack functional p53 protein are arrested in the G(2) phase of the cell cycle due to DNA damage. It was previously found that the human promyelocyte leukemia cells HL-60 (TP53 negative) that had been exposed to ionizing radiation at doses up to 10 Gy were arrested in the G(2) phase for a period of 24 h. The radioresistance of HL-60 cells that were exposed to low dose-rate gamma irradiation of 3.9 mGy/min, which resulted in a pronounced accumulation of the cells in the G(2) phase during the exposure period, increased compared with the radioresistance of cells that were exposed to a high dose-rate gamma irradiation of 0.6 Gy/min. The D(0) value (i.e. the radiation dose leading to 37% cell survival) for low dose-rate radiation was 3.7 Gy and for high dose-rate radiation 2.2 Gy. In this study, prevention of G(2) phase arrest by caffeine (2 mM) and irradiation of cells with low dose-rate irradiation in all phases of the cell cycle proved to cause radiosensitization (D(0)=2.2 Gy). The irradiation in the presence of caffeine resulted in a second wave of apoptosis on days 5-7 post-irradiation. Caffeine-induced apoptosis occurring later than day 7 post-irradiation is postulated to be a result of unscheduled DNA replication and cell cycle progress.
Keywords: dávka záření; viabilita buněk; HL-60 buňky; Adaptation, Physiological; Caffeine; vztah mezi dávkou a účinkem léčiva; Cell Survival; fyziologická adaptace; Radiation Dosage; analýza kolonii tvořících jednotek; Dose-Response Relationship, Radiation; kofein; lidé; HL-60 Cells; tolerance záření; Humans; Cell Cycle; apoptóza; Radiation Tolerance; vztah dávky záření a odpovědi; buněčný cyklus; Radiation-Sensitizing Agents; Dose-Response Relationship, Drug; Apoptosis; Colony-Forming Units Assay; radiosenzibilizující látky